Assessment of the Telomere Length and Its Effect on the Symptomatology of Parkinson's Disease - Tina Levstek; Sara Redenšek; Maja Trošt; Vita Dolžan; Katarina Trebušak Podkrajšek (MDPI AG, 2021)
Telomeres, which are repetitive sequences that cap the end of the chromosomes, shorten with each cell division. Besides cellular aging, there are several other factors that influence telomere length (TL), in particular, oxidative stress and inflammation, which play an important role in the pathogenesis of neurodegenerative brain diseases including Parkinson's disease (PD). So far, the majority of studies have not demonstrated a significant difference in TL between PD patients and healthy individuals. However, studies investigating the effect of TL on the symptomatology and disease progression of PD are scarce, and thus, warranted. We analyzed TL of peripheral blood cells in a sample of 204 PD patients without concomitant autoimmune diseases and analyzed its association with several PD related phenotypes. Monochrome multiplex quantitative PCR (mmqPCR) was used to determine relative TL given as a ratio of the amount of DNA between the telomere and albumin as the housekeeping gene. We found a significant difference in the relative TL between PD patients with and without dementia, where shorter TL presented higher risk for dementia (p = 0.024). However, the correlation was not significant after adjustment for clinical factors (p = 0.509). We found no correlations between TLs and the dose of dopaminergic therapy when the analysis was adjusted for genetic variability in inflammatory or oxidative factors. In addition, TL influenced time to onset of motor complications after levodopa treatment initiation (p = 0.0134), but the association did not remain significant after adjustment for age at inclusion and disease duration (p = 0.0781). Based on the results of our study we conclude that TL contributes to certain PD-related phenotypes, although it may not have a major role in directing the course of the disease. Nevertheless, this expends currently limited knowledge regarding the association of the telomere attrition and the disease severity or motor complications in Parkinson's disease.